Experimental Investigation of a MopFan-Based Photocatalytic Air Purification Device. (12th May 2022) - Tapia-Brito, Emmanuel; Riffat, James; Wang, Yixin; Ghaemmaghami, Amir M.; Coleman, Christopher M.; Riffat, Saffa
Photocatalytic oxidation (PCO) is a potential approach for air cleaning, especially when utilising titanium dioxide (TiO2). A MopFan is similar to a roller brush but is made of flexible fibres coated with TiO2. Unlike conventional filter/mesh UV systems, a MopFan provides a wide UV-TiO2 interaction surface area and airflow passage. This revolutionary technique can be low cost, efficient, and potentially effective against viruses, making it suitable for cleaning indoor air. It is easy to use but technically advanced. The system may be mounted on walls, floors, or placed on desktops. A photocatalytic air purification based on MopFan prototype was designed, constructed and tested. This study utilised copper wires (0.1 mm, 0.3 mm, 0.4 mm, and 0.5 mm), plastic fibres (0.5 mm and 1.1 mm), brass wire (0.4 mm), steel wire (0.38 mm), and organic "coco" fibres (0.4 mm). Copper wire (0.5 mm) and organic fibre (0.4 mm) were found to be effective against SARS-CoV-2, but brass (0.4 mm) and plastic (0.5 mm) fibres were found only partially effective. The purification performance was compared using MopFan with plastic (0.5 mm), brass (0.4 mm) and organic "coco" (0.4 mm) fibres but the other materials were rejected due to their poor qualities or difficulties in manufacturing. It was found that the system has a better effectiveness with organic fibres, around 21% of reduction consistently throughout the test. It was also found that by using the photocatalytic MopFan air cleaning system, the final concentration of pollutants in a room is determined by the rate and concentration of pollutant generation. Highlights: Organic fibres do not require sanding prior to being coated with TiO2 solution. Copper and organic fibres are effective SARS-CoV-2 inhibitors. Organic fibres are the most efficient for air purification. The performance of purification is related to the concentration of pollutants.